KINERJA BADAN PENANGGULANGAN BENCANA DAERAH KABUPATEN KETAPANG DALAM MENANGGULANGI KEBAKARAN HUTAN DAN LAHAN DI KABUPATEN KETAPANG - JANUARDI, JANUARDI; Sunyata, Lina; Rasidar, Rasidar (PublikA Jurnal Ilmu Administrasi Negara (e-Journal), 2023)
The purpose of this research was to describe the performance of the Regional Disaster Management Agency of Ketapang Regency in handling forest and land fires in Ketapang Regency. The problem of forest and land fires was a very interesting problem to study because forest and land fires in Ketapang Regency were increasing and causing many negative impacts for humans, the environment and the ecosystem. In this research, the researcher used qualitative descriptive method with the theory of performance indicators from Dwiyanto (2017: 50), namely: 1.) Productivity, productivity was not maximized, because the target had not gotten the results as expected, in addition to the ineffective and inefficient firefighting. 2.) Service Quality, the service quality was considered quite good because the community was satisfied with the services of the BPBD of Ketapang Regency. 3.) Responsiveness, the responsiveness was quite good which was indicated by the fairly fast response from the BPBD of Ketapang Regency when receiving reports of forest and land fires from a place. 4.) Responsibility, the responsibility was considered suboptimal because the personnel did not carry out the firefighting activities in accordance with the SOP (Standard Operating Procedure) to the fullest. 5.) Accountability, the accountability was considered quite good because the BPBD of Ketapang Regency carried out forest and land fire management fairly and prioritized human values existing in the community.Â Keywords: Organizational Performance, BPBD, Handling Forest and Land Fires, Ketapang Regency.Â Â